Motivasi Peserta Didik Dalam Mengikuti Pembelajaran PJOK Pada Masa Pandemi Covid-19 - Marisa Aprilia Kartika Dewi (Universitas Syiah Kuala, 2022)
This study aims to analyze and examine the motivation of students in participating in PJOK learning during the Covid-19 pandemic. This study uses a quantitative approach and uses a descriptive design by means of a survey technique. The sample in this study was taken 151 students. This study uses a questionnaire filling technique, the results of the study state that, (1) those in the very low category are 8 students reaching 5.3%, (2) those in the low category are 35 students reaching 23.2%, ( 3) those in the medium category reached 47.7%, (4) those in the high category were 22 students reached 14.6%, and (5) those included in the very high category were 14 students reached 9.3 %. The results of the study contain the influence of motivation on learning and this motivation can be classified as moderate category at SMP Negeri 8 Malang in class VII.Keywords: motivation; covid-19; sports physical education and health